Process performance and quality attributes of temperature and step-down relative humidity controlled hot air drying of Panax notoginseng roots - Jiang, Dalong; Li, Congcong; Zielinska, Sara; Liu, Yanhong; Gao, Zhenjiang; Wang, Rongyan; Zheng, Zhian (International Journal of Agricultural and Biological Engineering, 2021)
The effects of temperature and step-down relative humidity controlled hot-air drying (THC-HAD) on the drying kinetics, energy efficiency and quality, i.e., rehydration ratio (RR), color parameters (L*, a*, b*), total color difference (ΔE*), Panax notoginseng saponins (PNS) content, and ginsenosides content (R1, Rg1, Re, Rd, Rb1) of Panax notoginseng roots were evaluated. The drying time was significantly affected by the drying temperature followed by the relative humidity (RH) of the drying air. Special combination of drying conditions, i.e., drying temperature of 50°C, relative humidity of 40% for 3 h and then continuous dehumidification from 40% to 8% allowed to shorten the drying time by 25% compared to drying at the same temperature and continuous dehumidification. The longer was the drying time under constant high RH of drying air, the lower was the RR of dried samples. The step-down RH strategy contributed to the formation of a porous structure, enhancement of drying efficiency and quality improvement. Generally, the ginsenosides content increased with the increase in temperature, while no obvious trend was recorded for ginsenoside R1. The contents of the ginsenoside R1, Rg1, Rb1 and PNS decreased with the increase in the drying time under constant high RH. Taking into account the drying time, energy consumption and quality attributes, drying at the temperature of 50°C, constant RH of 40% for 3 h and then step-down RH from 40% to 8% was proposed as the most favorable combination of drying conditions for dehydration of whole Panax notoginseng roots.Keywords: Panax notoginseng (Burk.) F. H. Chen (Araliaceae) roots, step-down relative humidity, hot air drying, process performance, quality attributeDOI: 10.25165/j.ijabe.20211406.6198Citation: Jiang D L, Li C C, Zielinska S, Liu Y H, Gao Z J, Wang R Y, et al. Process performance and quality attributes of temperature and step-down relative humidity controlled hot air drying of Panax notoginseng roots. Int J Agric & Biol Eng, 2021; 14(6): 244–257.